2020
DOI: 10.1111/jppi.12358
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and Linguistic Diversity Among Children and Families Referred for Diagnostic Evaluation of Developmental Delay and Disability: Implications for Service Delivery

Abstract: A significant proportion of health‐ and disability‐sector consumers in Australia speak a language other than English (LOTE) at home. Barriers to service access in culturally and linguistically diverse (CALD) populations are acknowledged; however, there is limited data to guide service delivery among care providers. The aims of the present study were to investigate the linguistic diversity of preschool‐aged children and families presenting for diagnostic assessment of developmental delay and disability at the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…In this study, we found significant association between CALD status and delayed age of concern as well as higher severity of autism traits (RRB domain and CSS scores). The main findings are in keeping with our previous research and other Australian study that found evidence for an ‘inverse care law’ in that, children from more disadvantaged backgrounds, including those from CALD background, who are at highest developmental risk, are least likely to access prevention and health promotion programs such as developmental surveillance, and they are late in seeking help for developmental issues [ 48 , 49 ]. As a result, there is a delay in initiation of intervention due to late diagnosis and thereby missed opportunities to maximise the plasticity of the developing brain [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found significant association between CALD status and delayed age of concern as well as higher severity of autism traits (RRB domain and CSS scores). The main findings are in keeping with our previous research and other Australian study that found evidence for an ‘inverse care law’ in that, children from more disadvantaged backgrounds, including those from CALD background, who are at highest developmental risk, are least likely to access prevention and health promotion programs such as developmental surveillance, and they are late in seeking help for developmental issues [ 48 , 49 ]. As a result, there is a delay in initiation of intervention due to late diagnosis and thereby missed opportunities to maximise the plasticity of the developing brain [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…Given that assessment services in the public sector are referred a significantly higher proportion of individuals with additional vulnerabilities (e.g. low socioeconomic status (SES), cultural and linguistic diversity) compared to those in the private sector (Lewis, 2021; Patel et al, 2021), these assessments may provide one of the only opportunities for children to receive multi-disciplinary and specialised assessment in their lifetime. It is critical that these assessments and subsequent reports give families information that can be utilised to adequately address the needs of children and their family.…”
mentioning
confidence: 99%